Primary intraosseous carcinoma arising in dentigerous cyst: Case report. (2020) - Marchal, Alix; Gérard, Éric; Curien, Rémi; Bourgeois, Geoffrey
Highlights: Primary intraosseous carcinoma arising in a dentigerous cyst is a rare observation. There are no clinical or radiological pathognomonic characteristics and the diagnosis is often made fortuitously. A surgical excision with clear margin is the cornerstone of treatment. A systematic and careful microscopic analysis of any cyst, even if look like benign, should be undertaken. Abstract: Introduction: Carcinomas arising in odontogenic cysts are uncommon. Malignant transformation of a dentigerous cyst is a rare observation. A primary intraosseous carcinoma from a dentigerous cyst in a 69 years old female is presented in this case report. Presentation of case: The patient initially consulted for pain in the mandibular left molar region. Primary investigations firstly showed a probably benign lesion but immunochemistry analysis finally revealed a squamous cell carcinoma arising in a dentigerous cyst. An extension assessment was performed and no evidence of lymph node extension or distant metastasis were found. A non-interrupting mandibular bone resection without neck dissection was realized. The patient made a good recovery after surgery without postoperative complication. No clinical symptoms or sign of local recurrence or metastasis was detected after 17 months follow-up. Discussion: PIOC arising in a dentigerous cyst is a rare observation. PIOC from odontogenic cysts have an incident rate of 0, 3 to 2% and only 16%–51% of them are PIOC from dentigerous cyst. There are no clinical or radiological pathognomonic characteristics. They often look like benign lesion and the diagnosis is often made fortuitously. A surgical excision with clear margin is the cornerstone of treatment. Clinical and radiological follow-up of the patient is recommended. Conclusion: This case underlines the importance of a systematic and careful microscopic analysis of any lesion, even benign at first sight. Surgeons and pathologists should be aware of the malignant potential of odontogenic cysts. This can modify the surgical management and the follow-up of the patient.